2018
DOI: 10.1021/acsmacrolett.7b00964
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Assembly of Cellulose Nanocrystals during Drying and Redispersion

Abstract: We have followed the structural evolution during evaporation-induced self-assembly of sulfonated cellulose nanocrystal (CNC) in the presence of H+ and Li+ counterions by small-angle X-ray scattering. Drying of CNC-H dispersions results in ordered films that could not be readily redispersed, while the CNC-Li films were disordered and prone to reswelling and redispersion. The scaling of the separation distance (d) between CNC particles and the particle concentration (c) shows that the CNC-H dispersions display a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…CNC and CNF can assemble into variety of different configurations (Kontturi et al 2018;Lagerwall et al 2014;Ding et al 2014;Orts et al 1998;Benselfelt et al 2019;Lombardo et al 2019;Honorato-Rios et al 2018). CNC can also self-assemble into chiral nematic phases which possess interesting photonic properties and may have applications as optical material (Schütz et al 2015;Surov et al 2017;Liu et al 2019Liu et al , 2018Pospisil et al 2018;Bertsch et al 2019;Parker et al 2016;Yao et al 2017). The reflected wavelengths of the chiral nematic phases are depended of the pitch (p) of the self-assembled CNC.…”
Section: Introductionmentioning
confidence: 99%
“…CNC and CNF can assemble into variety of different configurations (Kontturi et al 2018;Lagerwall et al 2014;Ding et al 2014;Orts et al 1998;Benselfelt et al 2019;Lombardo et al 2019;Honorato-Rios et al 2018). CNC can also self-assemble into chiral nematic phases which possess interesting photonic properties and may have applications as optical material (Schütz et al 2015;Surov et al 2017;Liu et al 2019Liu et al , 2018Pospisil et al 2018;Bertsch et al 2019;Parker et al 2016;Yao et al 2017). The reflected wavelengths of the chiral nematic phases are depended of the pitch (p) of the self-assembled CNC.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, when a system is compressed isotropically in 3D, the separation distance will decrease as % <9/Q . 32 According to the fitting results, the exponent of ξ (-0.35) is very close to the -1/3. Considering the nematic phases are randomly oriented in 3D to a large extent in our system, the decrease of ξ reflects a reduction of fiber to fiber distance in the nematic phase, which is equivalent to the isotropic shrinkage of a general 3D CNF network.…”
mentioning
confidence: 61%
“…The intriguing capability of CNCs to self‐assemble into chiral nematic iridescent films with a helical structure and their photonic properties and applications have attracted increasing attention . Many research efforts have been put on the control of their optical properties .…”
Section: Introductionmentioning
confidence: 99%
“…The cholesteric liquid crystalline phase formed by CNCs has been used as a template to synthesize novel chiral materials for advanced optical applications. [11b,20] Most recently, Xu et al reported that chiral photonic CNC films can be used for ultrasecure polarization‐based encryption, which will pave the way to develop the next‐generation advanced photonic devices . Although some researchers have used different acid especially the mineral acid to obtain the CNCs, to the best of our knowledge, so far no one has reported the direct use of the synergistic effect of mineral sulfuric acid coupling organic acid hydrolysis to tailor the chiral nematic structure of CNC iridescent films.…”
Section: Introductionmentioning
confidence: 99%